2019
DOI: 10.4103/ams.ams_145_18
|View full text |Cite
|
Sign up to set email alerts
|

Extraskeletal myxoid chondrosarcoma of the parotid gland

Abstract: Extraskeletal myxoid chondrosarcoma (EMC) is a rare tumor with an estimated incidence of <3% among of all soft-tissue sarcomas. It is characterized by a multinodular architecture, abundant myxoid matrix, and malignant chondroblast-like cells arranged in cords. The tumor is an entity from chondrosarcomas of bones, commonly found in the soft tissues of the lower extremities at 80%. There are very limited reports of this tumor in the head and neck, especially in the parotid gland. The purpose of this paper is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…Approximately 20% of the cases are located in the trunk, mainly in skeletal muscles, tendons and the deep subcutis; a few cases involve the skin and bone tissue, whereas rare sites include the vulva and the breast [ 5 , 6 ]. After we retrospect 48 cases from 1981–2022 which took place in the head and neck region [ 1 , 7 ], we found that males account for 60.4%( n = 29), while females make up 37.5%( n = 18), and 2.1%( n = 1 case) was unavailable, the male-to-female ratio of about 1.5:1 (Fig. 5 A).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 20% of the cases are located in the trunk, mainly in skeletal muscles, tendons and the deep subcutis; a few cases involve the skin and bone tissue, whereas rare sites include the vulva and the breast [ 5 , 6 ]. After we retrospect 48 cases from 1981–2022 which took place in the head and neck region [ 1 , 7 ], we found that males account for 60.4%( n = 29), while females make up 37.5%( n = 18), and 2.1%( n = 1 case) was unavailable, the male-to-female ratio of about 1.5:1 (Fig. 5 A).…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of EMC remains controversial. Surgical or accidental trauma may be key factors, along with the inhalation of chemical carcinogens such as hydrocarbons [ 1 , 7 ]. Our patient did not report any intraoral region trauma.…”
Section: Discussionmentioning
confidence: 99%
“…er extremities (80%) and the superficial trunk (20%) [4]. Soft tissue sarcoma (STS) are rare tumors, with a variety of histological subtypes characterized by peculiar clinical features and specific therapeutic options [5].…”
Section: Case Reportmentioning
confidence: 99%
“…2,3 It rarely occurs in solid organs. 4,5 Extraskeletal myxoid chondrosarcoma has a low to moderate malignant potential and exhibits local recurrence rates ranging from 37% to 48% and distant metastasis rates ranging from 13% to 46%. 6 Previous study reported moderate FDG uptake (2.8-7.4) in extraskeletal myxoid chondrosarcoma, 7 which aligns with the findings observed in this case.…”
mentioning
confidence: 99%
“…Extraskeletal myxoid chondrosarcoma is a rare mesenchymal tumor with unclear differentiation, which tends to occur in the proximal limb 2,3. It rarely occurs in solid organs 4,5. Extraskeletal myxoid chondrosarcoma has a low to moderate malignant potential and exhibits local recurrence rates ranging from 37% to 48% and distant metastasis rates ranging from 13% to 46% 6.…”
mentioning
confidence: 99%